Association Between Neonates With Laryngomalacia and Neonatal Abstinence Syndrome. (September 2022) - Abraham, Elizabeth J.; Danis, David O'Neil; Levi, Jessica R.
Objective: Laryngomalacia (LM) is the most common congenital anomaly of the larynx. The cause of LM is still largely unknown, but a neurological mechanism has gained the most acceptance. There have not been any studies examining the prevalence of LM in infants with Neonatal Abstinence Syndrome (NAS). The aim of our study is to determine if infants with NAS are more likely to be diagnosed with LM. Methods: This study was a population-based inpatient registry analysis. We examined nationwide neonatal discharges in 2016 using the Kids' Inpatient Database (KID). Only patients listed as neonates were included. The International Classification of Diseases, 10th revision, Clinical Modification (ICD-10-CM) codes for neonatal withdrawal symptoms from maternal use of drugs of addiction (P96.1) and diagnoses denoting LM were used. To quantify associations between the LM and NAS groups, prevalence rates and odds ratios (ORs) were used. Results: There were 3 970 065 weighted neonatal discharges in the 2016 KID. Among patients included in our dataset, 0.809% (32 128) had NAS and 0.075% (2974) had LM. There was an increased odds ratio for neonates with NAS and LM (OR of 2.85, 95% CI = 2.24-3.63) compared to infants without NAS. Multiple logistic regression accounting for possible confounders produced an adjusted OR of 1.68 (95% CI = 1.29-2.19). Conclusion: Our study found an association between NAS and LM. This suggests that prenatal exposure to opioids or possibly the sequelae of withdrawal symptoms may be risk factors for the development of LM.